Phenol Adsorption and Photo-Oxidation on Porous Carbon/Titania Composites - Leticia F. Velasco; José B. Parra; Conchi O. Ania (Adsorption Science & Technology)
Carbon/titania composites with different loadings were prepared and investigated for phenol adsorption and photo-oxidation from dilute aqueous solutions. The rate of phenol adsorption increased when titanium oxide (P25, Degussa) was immobilized on the carbon support due to the porous features of the resulting C/TiO 2 composites. The kinetics of phenol adsorption were very fast for samples containing low titanium oxide contents, whereas titania loadings above 20 wt% presented some operational problems that prevented their application in aqueous solutions. Those C/TiO 2 composites which exhibited higher adsorption rates in the absence of illumination also showed a more rapid disappearance of phenol from aqueous solution under UV light, together with the formation of lower amounts of intermediates. Removal efficiencies close to 100% were obtained for C/TiO 2 composites containing ca. 10–15 wt% titanium oxide, with preferential oxidation of phenol through the formation of catechol.